Weight gain, but not macronutrient intake, modifies the effect of dietary branch chain amino acids on the risk of metabolic syndrome. (March 2020) - Hosseinpour-Niazi, Somayeh; Tahmasebinejad, Zhale; Esfandiar, Zohre; Bakhshi, Bahar; Mirmiran, Parvin; Azizi, Fereidoun
Highlights: The association between dietary BCAA and risk of MetS are unclear. Weight change modulates the association between dietary BCAAs and risk of MetS. Macronutrient did not affect the association between dietary BCAAs and risk of MetS. Abstract: Aims: The aim of this study was to investigate whether both weight change and the background intakes of macronutrient modulate the association between dietary branch chain amino acids (BCAAs) and the risk of metabolic syndrome (MetS). Methods: This prospective study was conducted within the framework of the Tehran Lipid and Glucose Study. BCAA intakes were collected using a valid and reliable semi-quantitative food frequency questionnaire. MetS components were defined according to the modified national Cholesterol Education Program Adult Treatment Panel III. Weight change was categorized as weight gain (≥ or <7% over 8.9 year follow-up). Dietary fat and carbohydrate intake were categorized as above/below the median intake. Results: Among participants with weight gain ≥ 7% during follow-up, intakes of both dietary BCAAs and its various sources (below or above the median intake) were associated with higher risk of MetS, compared with subjects with lower intakes of BCAAs and weight change ≤ 7%. Background dietary fat and carbohydrate did not modify the association of dietary BCAAs and its various sources with the risk of MetS. Conclusions: Weight change, but not dietary macronutrient intake, modulates the association between dietary BCAAs and risk of MetS among adults.